1987
DOI: 10.3382/ps.0661558
|View full text |Cite
|
Sign up to set email alerts
|

Research Note: Effect of Breeder Quail Age and Egg Weight on Chick Weight

Abstract: An experiment was conducted with 546 Japanese breeder quail to determine the effect of age and egg weight on day-old chick weight over a 16-wk reproduction period. Weight of chicks hatched from the same or different size eggs was found to be affected by parental age. The largest increase in chick weight occurred after 10 wk of age. It was found that egg weight did not affect the hatching weight if egg weight was above 11 g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 11 publications
1
9
1
1
Order By: Relevance
“…In terms of body weight, the differences between wild-type and white, dark brown, and golden quail were 5.4, 8.3, and 7.6 g, respectively. This result is similar to findings of Yannakopoulos and Tserveni-Gousi (1987) and Tserveni-Gousi (1987). White-color quails had lighter LW than the wild-type.…”
Section: Discussionsupporting
confidence: 89%
“…In terms of body weight, the differences between wild-type and white, dark brown, and golden quail were 5.4, 8.3, and 7.6 g, respectively. This result is similar to findings of Yannakopoulos and Tserveni-Gousi (1987) and Tserveni-Gousi (1987). White-color quails had lighter LW than the wild-type.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, neither the PRESI nor the breeder age significantly influenced the subsequent body weight of the progeny. The result for the progeny body weight was not similar with the findings of Shanawany [16], Tserveni-Gousi [21] and Yannakopoulos et al [23], who reported that the weight gain of chicks can be affected by parental age. Egg storage for 15 d significantly depressed the body weight of quail probably due to an increase of second grade chicks at hatch after prolonged storage time.…”
Section: Discussioncontrasting
confidence: 81%
“…These results can also be because larger eggs have higher yolk weights and higher phospholipid and protein contents at the end Influence of European Quail Breeders Age on Egg Quality, Incubation, Fertility and Progeny Performance of the incubation period, when there is a transfer of nutrients from the yolk sac to the embryo, and result in larger chicks at hatch and better development of birds during the rearing period (Noble et al, 1986;Ding & Lilburn, 1996). Analyzing Japanese quail breeders from 42 to 154 days, Yannakopoulos & Tserveni-Gousi (1987) described a positive correlation between chick weight and egg weight. Breeders between 70 and 120 days laid larger eggs (12.4g), with better hatchability (72.2%) and larger chicks when compared to the other age groups analyzed.…”
Section: Influence Of European Quail Breeders Age On Egg Quality Incmentioning
confidence: 99%